Biosensor Response at Mixed Enzyme Kinetics and External Diffusion Limitation in Case of Substrate Inhibition - Kulys, J. (Nonlinear Analysis: Modelling and Control, 2006)
The action of a biosensor containing non Michaelis-Menten enzyme was modeled at mixed enzyme kinetics and external diffusion limitation in the case of substrate inhibition. The calculations show that at the electrode surface multi steady-state concentrations of substrate may be generated if diffusion module is much larger than 1 and the substrate bulk concentration is much bigger than Michaelis-Menten parameter. The multi steady-state concentration generates multi response of the biosensor. The production of the multi steadystate may cause the biosensor response oscillation.